Pengaruh Kepuasan Kerja dan Komitmen Organisasi Terhadap Keinginan Berpindah Karyawan PT. Delami Garmen Kota Bandung - Wandy Zulkarnaen; Yayan Sofyan (Universitas Bina Sarana Informatika, 2018)
The purpose of this research is to find out how much influence job satisfaction and organizational commitment to desire to move simultaneously and partially at PT. Garment. The author uses research methods based on descriptive and verification analysis.